The Power of Legal Certainty in the Trademark Exhaustion Principle Governing Parallel Imports - Alif Muhammad Gultom; Dodik Setiawan Nur Heriyanto (Universitas Muhammadiyah Malang, 2023)
The exhaustion doctrine in intellectual property law refers to the limitation imposed on the rights of owners to enforce their intellectual property rights after a particular point of sale. It creates a framework for determining the legality of parallel imports and helps to balance the interests of intellectual property owners and consumers. This paper presents a comparative study on the trademark exhaustion principle and parallel import between the European Union (EU) and Indonesia. The study investigates the legal framework and the practical application of these concepts in both jurisdictions. This study uses a normative research method and a legal comparative approach to analyze and describe the legal frameworks of different jurisdictions. The research findings indicate that the EU has a well-defined threshold for the exhaustion of trademark rights, which is aligned with the regional exhaustion principle. In contrast, the Indonesian legal system lacks clarity on this principle, which creates confusion and uncertainty for trademark owners and parallel importers. Last, this research also provides insights for policymakers, practitioners, and academics who are interested in the current exhaustion principle and parallel import development.